Kekerasan Bahasa di Media Daring Nasional - Wayan Pageyasa (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2023)
Verbal abuse means impolite, referring to Leech's politeness principle. The problem of this research is: how is language violence in the Indonesian National Brave media? The long-term goal of this research is to prevent conflicts that occur in Indonesia due to hatred. The target of this research is to obtain reliable findings about patterns of language violence in Indonesia's national online media. The method used is pragmatic content analysis. The results of the research show that language violence predominantly occurs in Indonesia's national online media. The violence of language is measured by its violation of the Principle of Politeness which consists of six maxims. Of the total 8,922 analyses, 3,852 complied and 5,070 were tracked. If we look at the analysis of comments for each topic, out of 100 topics, only 16 topics tend to have comments that comply with the principles of politeness and 84 topics tend to violate them. From the research findings, it was also revealed that language violence predominantly occurs on topics related to political issues. While the topics relate to entertainment and the arts, there is rarely any violent language. This research also reveals that language violence has grown rapidly since the 2014 presidential election.